Querido Maestro: el epistolario inédito de Ángel Guido a Ricardo Rojas. Entre la arquitectura euríndica y el archivo - Antequera, María Florencia (Confluenze. Rivista di Studi Iberoamericani, 2019)
This work is aimed to analyze some keys of the unpublished collected letters from the polemical Rosarino architect Angel Guido (1896-1960) to Ricardo Rojas (1882-1957). We analyze the features molding the collection together with the thematic main ideas shining in the letters. We explore certain relations between the unpublished texts that make up Guido’s document collection and his theoretical writings related to the “eurindica” conception. We try to enhance the borders of Guido’s work by discussing how letters, architectural production, literary writings and theoretical texts are gathered in the same constellation.